Development of a new generation flotation cell and monitoring of air bubbles - Aytac, Ayca; Tuna, Muhammed Cihat (Iwa Publishing, 2023)
The flotation process allows particles and oil to separate from wastewater with high efficiency. Therefore, it is widely used in engineering and is a multidisciplinary field of study. In this study, a new generation flotation method is developed as an alternative to conventional flotation methods. Some experiments are conducted to determine the performance of this new system. It is known that the air-demand rate in the flotation process directly improves flotation performance. For this purpose, maximum aeration efficiency and bubble properties in the flotation cell supported by the newly developed head gated conduit are examined. A pilot-scale flotation system is installed for the experimental study. With the help of high resolution and high-speed cameras, parameters such as air bubble density, air bubble size, dead zone volume and penetration depth are determined. In addition, the images recorded during the flotation process are examined with professional image processing techniques. Experimental results showed that the Froude number, jet plunge angle and cell water levels have a significant impact on air-demand in the new system.
Keywords: air bubble; air-demand ratio; flotation cell; Froude number; head gated conduit; hydraulic structures